2018
DOI: 10.1007/s10151-018-1781-6
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of minimally invasive surgery for retrorectal tumors

Abstract: Retrorectal tumors are rare tumors that require resection for symptoms, malignancy and potential malignant transformation. Traditional approaches have included laparotomy, perineal excision or a combination. Multiple minimally invasive techniques are available which have the potential to minimize morbidity and enhance recovery. We performed a systematic review of the literature to determine the feasibility and surgical outcomes of retrorectal tumors approached using minimally invasive surgical techniques. Publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 46 publications
1
37
0
4
Order By: Relevance
“…To our knowledge, this is the first reported case in Australia and New Zealand. Worldwide, there have been case reports of robotic resection of retrorectal tumours 5 6…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first reported case in Australia and New Zealand. Worldwide, there have been case reports of robotic resection of retrorectal tumours 5 6…”
Section: Introductionmentioning
confidence: 99%
“…Complete surgical removal of epidermal cysts and other retrorectal tumors is the only treatment option. Surgery is indicated when signs and symptoms are suspicious of either compression of the surrounding structures and malignant transformation or to prevent common complications such as infections and fistula formation [5,12]. Moreover, surgical resection is also recommended to establish a definitive diagnosis, as evident in our case.…”
Section: Discussionmentioning
confidence: 80%
“…[2,3] Studies have also shown there to be shorter operative and recovery times with the robotic approach. [2,[4][5][6] Decreased post-operative pain and blood loss have also been appreciated. [2,6] Finally, based on available data, the post-operative outcome is similar for robotic and laparoscopic resection.…”
Section: Discussionmentioning
confidence: 99%
“…[2,6] Finally, based on available data, the post-operative outcome is similar for robotic and laparoscopic resection. [4,5] An additional benefit of the abdominal approach is the decreased risk of perineal wound complications. Such complications include formation of rectocutaneous fistulas and wound infections, sequelae of which could be necessity for colostomy creation and administration of intravenous antibiotics, respectively.…”
Section: Discussionmentioning
confidence: 99%